Kinetics and mechanism of large rate enhancement in the Alkaline Hydrolysis of N '-Morpholino-N-(2'-Methoxyphenyl)Phthalamide - Ariffin, Azhar; Khan, M.N.; Sim, Y.L. (2008)
The apparent second-order rate constant (k(OH)) for hydroxide-ion-catalyzed conversion of 1 to N-(2'-methoxyphenyl)phthalamate (4) is similar to 10(3)-fold larger than k(OH) for alkaline hydrolysis of N-morpholinobenzamide (2). These results are explained in terms of the reaction scheme 1 -> 3 -> 4 where 3 represents N-(2'-methoxyphenyl)phthalimide and the values of k(2obs)/k(1obs) Vary from 6.0 x 10(2) to 17 x 10(2) within [NaOH] range of 5.0 x 10(-3) to 2.0 M. Pseudo-first-order rate constants (k(obs)) for alkaline hydrolysis of 1 decrease from 21.7 x 10(-3) to 15.6 x 10(-3) s(-1) with an increase in ionic strength (by NaCl) from 0.5 to 2.5 M at 0.5 M NaOH and 35 degrees C. The values of k(obs), obtained for alkaline hydrolysis of 2 within [NaOH] range 1.0 x 10(-2) to 2.0 M at 35 degrees C, follow the relationship k(obs) = k(OH)[HO(-)] + k(OH)'[HO(-)](2) with least-squares calculated values of k(OH) and k(OH)' as (6.38 +/- 0.15) x 10(-5) and (4.59 +/- 0.09) x 10(-5) M(-2) s(-1), respectively. A few kinetic runs for aqueous cleavage of 1, N'-morpholino-N-(2'-methoxyphenyl)-5-nitrophthalamide (5) and N'-morpholino-N-(2'-methoxyphenyt)-4-nitrophthalamide (6) at 35 degrees C and 0.05 M NaOH as well as 0.05 M NaOD reveal the solvent deuterium kinetic isotope effect (= k(obs)(H2O)/k(obs)(D2O)) as 1.6 for 1, 1.9 for 5, and 1.8 for 6. Product characterization study on the cleavage of 5, 6, and N-(2'-methoxyphenyl)-4-nitrophthalimide (7) at 0.5 M NaOD in D(2)O solvent shows the imide-intermediate mechanism as the exclusive mechanism.